Statement of the AGO and AG-CPC on the Aftercare/Follow-up for Surgical Procedures of the Lower Genital Tract after the Introduction of a New Cancer Screening Guideline - Hillemanns, Peter; Tempfer, Clemens; Beckmann, Matthias W.; Küppers, Volkmar; Quaas, Jens (Geburtshilfe und Frauenheilkunde, 2020)
The new guideline on organized cancer screening programs has been in force in Germany since January 1st, 2020. The guideline has amended earlier recommendations on cytological examinations, which were previously carried out annually during screening. The guidelines-based recommendations on the appropriate follow-up for preinvasive and invasive lesions of the uterine cervix and endometrium are briefly outlined and differentiated from screening cytology and Pap/HPV co-testing as described in the guideline on organized cancer screening programs (oKFE-RL).Die neue Richtlinie für organisierte Krebsfrüherkennungsprogramme ist in Deutschland seit dem 01.01.2020 in Kraft. Die bisher im Rahmen des Screenings erfolgten jährlichen zytologischen Untersuchungen wurden durch die neue Richtlinie geändert. Die leitlinienbasierten Empfehlungen zur Nachsorge bei präinvasiven und invasiven Erkrankungen der Cervix uteri und des Endometriums werden dargestellt und von der Screeningzytologie bzw. Pap/HPV-Ko-Testung gemäß oKFE-RL abgegrenzt.
Keywords: cervical cancer; organized cancer screening; follow-up; endometrial cancer; guideline